La edad en las primigesta como factor de riesgo en la morbi-mortalidad materna perinatal, Hospital Regional del Amazonas Iquitos – Perú – 1991 - Soto del Águila, Mercedes del Carmen (1992)
The present study is a descriptive, cross-sectional and prospective study conducted at the Maternity Service from the Department of Gynecology and Obstetrics Hospital Regional Amazon Iquitos, Peru, in the period from March to November 1991. It was found that during this period, there were a total of 1,548 pregnant women who were admitted in labor, of which 400 were for primigesta, where 104 (26%.) Were adolescents under 18 years, 10 (2.5%.) Añoseas of 35 years later and 286 (71.5%) comprised the control group 18 to 34 years In both groups studied, a high index of conditions encountered during pregnancy, childbirth and postpartum. Stressed during pregnancy toxemia and premature roptura of membranes, labor dystocia contraction and presentation for the teenager. Was aged for contraction and the pelvis. In the postpartum uterine atony for the group of añosas and complications of infectious type for adolescents. No maternal death was found in the study group and control The spontaneous vaginal delivery was more frequent in the group of adolescent and control; Caesarean section was more frequent in the añosas. The instrumental delivery was more frequent in the control group the study. Most newborns in the study and control groups were appropriate weights, good-minute Apgar gives life and went to term. Hypoxia, cephalohematoma and neonatal infection were the most common neonatal morbidities in the study groups. Preterm delivery occurred more frequently in the group of añosas and control, this being the main cause of perinatal death.